Mengembangkan Loyalitas Melalui Strategi Kualitas Layanan dan Kepercayaan Pada Industri Perbankan - Ferdian Hendrasto (Program Pascasarjana Universitas Gajayana, 2018)
Service quality has long been used to determine loyalty, with excellent service quality, it is expected that customer will be more likely to do repurchase. Another factor which affect loyalty is trust. The purpose of this research is to analyze the effect of service quality and trust to loyalty in banking industry. 100 customer are invited as respondents in this research. This associative research consist of two independent variables, they are service quality (X1) and Trust (X2) and one dependent variable which is loyalty (Y). For data collection purpose, library research and field research are conducted thoroughly. Data analysis method used in this research is reliability test and validity test. And then we conduct normality test and multicolinearity test. To analyze the hypothesis used in this research, we use simple regression analysis with t-test and multiple regression analysis with F-test. The result of this research shows that service quality (X1) is significantly influential to Loyalty (Y). trust (X2) is significantly influential to loyalty (Y). Finally, service quality (X1) and trust (X2), simultaneously, are significantly influential to loyalty (Y).